PRAGMATISM IN THE RELATIONSHIP BETWEEN NATIONAL INTERESTS AND STRATEGY - Forca, Božidar (National interest, 2026)
International relations are a changing field with no final solutions. Although they are not the only ones, states were and remain the key subject of international relations. The term state security was replaced by national security in the second half of the 20th century. It is not just a formal linguistic change in determining the security of the state. Namely, national interests came to the fore. Concepts of national values, interests, and goals emerge at different stages of the development of human society and the state. It is a fact that classical and medieval philosophy did not know the concept of interests, even national ones. This concept originates in the philosophy of pragmatism, and it occupies a central place and suppresses values. In this sense, national interests are a political category and the root cause of conflicts in international relations. The United States of America was the world's most powerful country in the 20th century. After the Second World War, a national security strategy document was created in the USA, in which, among other things, America's vital national interests and the way to achieve them are determined. From President Harry Truman to Donald Trump, the basic national interest of the USA has been and remains - to rule the world. The difference lies only in the methods of determination and operationalization, as well as in their application in practice. America remained the only superpower at the end of the Cold War. In this sense, the majority of European countries are joining American-led integration, primarily through NATO. In this sense, the majority of countries in Europe and around the world adopt national security strategies, except multinational states (organizations) that do not include the attribute "national" in their security strategies. It is a fact that in all the national security strategies of numerous countries, national interests and goals occupy a dominant place, while national values ​​are only sporadically mentioned.Analyzing the way of determining national interests and goals, as well as their realization and realization in practice, it can be unequivocally concluded that the world powers apply a direct and immediate approach to their determination, which is confirmed by their realization in practice. On the other hand, small and underdeveloped countries approach the determination of national interests and goals formally, so their realization in practice is questionable.The Republic of Serbia marks two decades of its independence and autonomy in very complex international relations. Serbia is going through a very difficult path of disintegration of the former SFRY, and that disintegration was not completed precisely on its territory - Kosovo and Metohija. Although the UN Security Council protectorate continues in Kosovo and Metohija, the temporary organs of the Albanian authorities proclaimed an independent Kosovo. Serbia has adopted two national security strategies, which are qualitatively very different. The attitude towards the way of determining national values, interests and goals is especially different. Thus, Serbia defined its national security for the first time only in 2019. In the relationship of national values, interests, and goals, there are evident inconsistencies and even a kind of exclusivity.
Keywords: National security strategy; National values; interests and goals